On sufficiency and duality for generalized quasiconvex nonsmooth programs - Mishra S.K. (My University, 2025)
For a nonsmooth multiobjective nonlinear program which involves inequality and equality constraints. Fritz John and Kuhn-Tucker type sufficient optimality conditions are obtained. Some duality theorems are also established for Mond-Weir type of duals. All results are given under generalized convexity assumptions.